Essays on Stock Issuance - Niklas Kohl (Copenhagen Business School (CBS), 2017)
Firms which issue new equity subsequently have lower returns than other firms, but does the strength of the issuance effect vary in the cross section of firms? The essay shows, that US firms with characteristics that makes them “hard to value” have returns which are strongly related to their past issuance activity, while the return of “easy to value” firms are less related to their past issuance activity. In most cases the difference between “hard to value” and “easy to value” firms are signiffcant. As proxies for “hard to value”, I use three different types of firm characteristics. First, I consider firms for which relatively little information is available as “hard to value”. Examples are firms covered by few analysts and small firms. Second, I consider firms with high levels of analyst disagreement on stock price target, next quarter earnings per share and share recommendation as “hard to value”. Third, firms with expected cash flows in the more distant future are “hard to value”. These include firms with low earnings, high asset growth, and low dividend yield.
hdl:10398/9536
Keywords: 650